Esporte competitivo: empatia ou vontade de vencer? - Ribeiro, Elizabeth Pedrosa (Universidade do Vale do Rio dos Sinos, 2017)
In competitive sport, the pursuit of victory seems to require athletes a degree of "immorality." Intentional simulations and fouls, as well as provocations and even aggressions are not exactly rare in collective sports; in individual sports, doping is a well-known example. Are these behaviors inherent in the practice of sports? Recent studies show, on the other hand, that such behaviors depend on a certain nullification or blockage of the empathic mechanisms in our brain. It seems that a "will to win" requires less empathy than morality requires. However, empathic feelings are fundamental conditions for appropriate moral behavior. On the other hand, for the competition to happen it is necessary that a will to win be manifest in those who are competing. This presents a problem for thinking about sport ethics, since the will to win can become a passion unimpeded. In this work, it is assumed that we are moral and empathetic beings by nature, but that empathy can be developed or repressed by a series of contingencies. On the other hand, we also assume that the will to win is one of those contingencies, being inherent in competition. Thus, what may or may not happen during a game seems to be directly related to the relevance of the result and its consequences. Hence, to conjugate empathy and the will to win means to conjugate moral variables eventually opposed, since both of them are necessary for the sport itself to exist. In this thesis, I will argue that, during a competition, it is inevitable that athletes express conflicting feelings and that there is an inherent tension in the sport between the will to win and empathy. These two impulses are always present in the sport, since they represent, on the one hand, the desire of the sportsman to be successful and, on the other, the desire to respect the adversary, in order to guarantee a fair competition. Combining these two features without making them void is perhaps the greatest value of competitive sport. In conclusion, I will argue metaethically that the sport example shows that a pluralist conception of values is closer to truth than a monistic conception.
Keywords: Ética no esporte; Competição esportiva; Vontade de vencer; Vitória; Empatia; Sport ethics; Sports competition; Will to win; Victory; Empathy; Fair play; ACCNPQ::Ciências Humanas::Filosofia